Crisis Inciting Carnivalesque: Early Childhood Teachers’ Political Dialogue Strategies - Westbrook, Fiona (SAGE Publications, 2024)
Early childhood education (ECE) teachers have expressed being silenced, indicating their responses to everyday issues of political concern may be hidden. This voicelessness underscores the importance of examining strategies and spaces that incite ECE teachers to vocalise their political dialogues. The pandemic, as a crisis event, within Victoria, Australia, during 2020 offers an unrivalled viewing of such entreaties. Posing unique and unusual dangers and opportunities, the early days of the pandemic serve as an entry point to viewing the strategies and spaces utilised by teachers during marked political crisis. Considering these pandemic dangers, this study undertakes a uniquely complex and opportunistic investigation into the political thoughts, ideas, and voices of ECE teachers within these coordinates, which may be of use for other community members beyond these dimensions. Comprising a larger doctoral study, teachers’ posts within a closed ECE Facebook group were analysed against Bakhtinian crisis chronotopes and carnivalesque responses. Insights infer the pandemic crisis incited teachers’ political dialogues to problematise their historical and ongoing issues. Doing so fostered a supportive peer network, opening up and renewing narratives from within the sector. Provocations to arise include the potential of crisis, the ability of laughter to empower teachers to speak up and have voice, as well as creating spaces for political dialogue and activism within the sector.
Keywords: 3903 Education Systems; 39 Education; 1303 Specialist Studies in Education; 1605 Policy and Administration; 1606 Political Science; 3902 Education policy, sociology and philosophy; 3903 Education systems